Optical laminate and picture display unit
The optical laminate stabilizes in-plane retardation characteristics and prevents metal corrosion in image display panels by using a polarizer, retarder, and adhesive layer with controlled moisture permeability and specific antistatic agents, addressing issues in conventional circularly polarizing plates.
Patent Information
- Application Number
- JP2024043930
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-08
- Filing Date
- 2024-03-19
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2044-03-19
AI Technical Summary
Conventional circularly polarizing plates experience changes in in-plane retardation characteristics due to iodine migration from the polarizer and antistatic agents in the adhesive layer, leading to hue changes and corrosion of metal members in image display panels, particularly at high temperatures.
An optical laminate comprising a polarizer, retarder, and adhesive layer with a specific ionic compound antistatic agent, along with protective films having controlled moisture permeability, to inhibit iodine and antistatic agent migration, thereby stabilizing retardation characteristics and preventing metal corrosion.
The solution effectively suppresses changes in in-plane retardation characteristics and prevents corrosion of metal members in image display panels, maintaining optical performance and device integrity over time.
Smart Images

Figure 2024177062000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and an image display device including the same. [Background technology]
[0002] In image display devices such as organic EL display devices, it is known that a circular polarizing plate is used to improve anti-reflection performance in order to suppress a decrease in visibility due to reflection of external light (for example, Patent Document 1). The circular polarizing plate is an optical laminate including a polarizer and a retarder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 160033 Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional circular polarizing plates have a problem that the in-plane retardation characteristics change with continued use, especially at high temperatures. The in-plane retardation characteristics refer to the retardation value of each wavelength and the wavelength dispersion, and changes in these cause changes in the reflected hue. In addition, when a circular polarizing plate is attached to an image display panel, a phenomenon has been observed in which the metal members of the image display panel are corroded due to some factor. In particular, when the adhesive on the panel attachment surface contains an antistatic agent, the above problem is likely to be significant. Therefore, the present invention aims to provide an optical laminate including a polarizer and a retarder, which can suppress changes over time in the in-plane retardation characteristics and suppress corrosion of the metal members of the image display panel to be attached. The present invention also aims to provide an image display device including the optical laminate. [Means for solving the problem]
[0005] The inventors of the present invention have considered that the cause of the change in the retardation characteristics of the conventional circular polarizing plate is the migration of iodine contained in the polarizer or the antistatic agent contained in the adhesive layer to the retarder. The inventors of the present invention have also considered that the cause of the corrosion of the metal members of the image display panel when the conventional circular polarizing plate is attached to the image display panel is the corrosion of the metal members caused by iodine contained in the polarizer or the antistatic agent contained in the adhesive layer. The inventors of the present invention have conducted research based on these ideas and have completed the invention shown below.
[0006] The present invention relates to an optical laminate comprising a first protective film, a polarizer, a second protective film, a retarder, and a pressure-sensitive adhesive layer in this order, the second protective film having a moisture permeability of 1200 g / (m 2 The pressure-sensitive adhesive layer contains an antistatic agent, and the antistatic agent contains an ionic compound composed of an organic cation and an anion represented by the following formula (1): (C n F 2n+1 SO2)2N - …(1) (In the formula, n is an integer of 0 to 5.)
[0007] This optical laminate can appropriately suppress the migration of iodine contained in the polarizer and the antistatic agent contained in the pressure-sensitive adhesive layer across layers in the optical laminate.
[0008] The optical stack may have one or more of the following features: The water vapor transmission coefficient of the retarder is 100 or less. The retarder includes a first retardation layer, a pressure-sensitive adhesive layer, and a second retardation layer, and functions as a λ / 4 plate over the entire visible light range. The adhesive layer is made of an active energy ray curing adhesive. The second protective film is made of a cyclic polyolefin resin. The thickness of the second protective film is 1 to 10 μm. The moisture permeability of the first protective film is 100g / (m 2·day) or more. · Ionic compounds contain organic cations that contain nitrogen atoms.
[0009] The present invention also provides an image display device comprising the above optical laminate and an image display panel to which the optical laminate is attached. Effect of the Invention
[0010] According to the present invention, it is possible to provide an optical laminate including a polarizer and a retarder, which can suppress a change over time in an in-plane retardation characteristic and can suppress corrosion of a metal member included in an image display panel to which the optical laminate is bonded. Also, according to the present invention, it is possible to provide an image display device including the optical laminate. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings.
[0013] <Optical laminate> (1) Overview As shown in FIG. 1, the optical laminate 1 of this embodiment is a circular polarizer comprising a linear polarizer 2, a phase shifter 4, and a pressure-sensitive adhesive layer 5 in this order. The term "circular polarizer" includes an elliptical polarizer. The optical laminate 1 can be used as an anti-reflection film in an image display device such as an organic electroluminescence (organic EL) display device. The linear polarizer 2 and the phase shifter 4 are laminated with a linear polarizer-phase shifter adhesive layer 3.
[0014] The linear polarizing plate 2 includes a first protective film 21, a polarizer 22, and a second protective film 23 in this order. A linear polarizing plate inner adhesive layer (not shown) is laminated between the first protective film 21 and the polarizer 22, and between the polarizer 22 and the second protective film 23. The linear polarizing plate inner adhesive layer is optional, and the first protective film 21 and the polarizer 22, and the polarizer 22 and the second protective film 23 may be in direct contact with each other.
[0015] Each component will be described in detail below.
[0016] (2) Polarizer The polarizer 22 is an optical film (linear polarizer) that transmits linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on the polarizer 22. Specifically, the polarizer 22 is a polyvinyl alcohol-based resin film (hereinafter also referred to as a "PVA-based film") in which a dichroic dye is adsorbed and oriented.
[0017] The polyvinyl alcohol resin (hereinafter also referred to as "PVA resin") constituting the PVA-based film can be produced by saponifying a polyvinyl acetate-based resin. The polyvinyl acetate-based resin can be a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group. In this specification, "(meth)acryl" means either acrylic or methacrylic. The "(meth)" in (meth)acrylate has the same meaning.
[0018] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually about 1000 to 10000, preferably about 1500 to 5000. The average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726 (1994). If the average polymerization degree is less than 1000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10000, the film processability may be poor.
[0019] A polarizer is usually produced through a process of uniaxially stretching a PVA-based film, a process of dyeing the PVA-based film with a dichroic dye to adsorb the dichroic dye, a process of treating the PVA-based film with the adsorbed dichroic dye with an aqueous boric acid solution to crosslink the film, and a process of washing the film with water after the crosslinking treatment with the aqueous boric acid solution (hereinafter also referred to as boric acid treatment).
[0020] The uniaxial stretching of the PVA-based film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. Of course, the uniaxial stretching can be performed in the multiple stages shown here. For the uniaxial stretching, a method of uniaxially stretching in the film transport direction between rolls having different peripheral speeds, a method of uniaxially stretching in the film transport direction using a heated roll, or a method of stretching in the width direction using a tenter can be adopted. The uniaxial stretching may be performed by dry stretching in the air, or by wet stretching in which the PVA-based film is stretched in a swollen state using a solvent such as water. The stretching ratio is usually about 3 to 8 times.
[0021] Dyeing of a PVA-based film with a dichroic dye can be carried out, for example, by immersing the PVA-based film in an aqueous solution containing the dichroic dye. As the dichroic dye, specifically, iodine or a dichroic organic dye is used. It is preferable that the PVA-based film is immersed in water and swelled before the dyeing process.
[0022] When iodine is used as the dichroic dye, a method of dyeing a PVA-based film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water, and the content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.
[0023] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of immersing a PVA-based film in an aqueous solution containing a water-soluble dichroic organic dye is usually used for dyeing. The content of the dichroic organic dye in this aqueous solution is usually about 0.0001 to 10 parts by mass, preferably 0.001 to 1 part by mass, per 100 parts by mass of water. This aqueous dye solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic organic dye solution used for dyeing is usually about 20 to 80°C. The immersion time in this aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.
[0024] The boric acid treatment after dyeing with a dichroic dye can be carried out by immersing the dyed PVA-based film in a boric acid-containing aqueous solution. The content of boric acid in the boric acid-containing aqueous solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, the boric acid-containing aqueous solution preferably contains potassium iodide. The content of potassium iodide in the boric acid-containing aqueous solution is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the boric acid-containing aqueous solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid-containing aqueous solution is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0025] The PVA-based film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated PVA-based film in water. The temperature of the water in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.
[0026] After washing with water, the polarizer is obtained by drying. The drying can be performed using a hot air dryer or a far infrared heater. The temperature of the drying is usually about 30 to 100°C, and preferably 50 to 80°C. The time of the drying is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content in the polarizer is reduced to a practical level by the drying. The moisture content is usually about 5 to 20 mass% and preferably 8 to 15 mass% with respect to the total mass of the polarizer. When the moisture content is 5 mass% or more, the polarizer has sufficient flexibility, and therefore, damage or breakage after drying can be suppressed. When the moisture content is 20 mass% or less, the polarizer has sufficient thermal stability.
[0027] In this manner, a polarizer in which a dichroic dye is adsorbed and oriented on a PVA film can be produced.
[0028] The luminosity-corrected polarization degree Py of the polarizer is usually 95% or more, preferably 97% or more, more preferably 98% or more, even more preferably 98.7% or more, still more preferably 99.0% or more, particularly preferably 99.4% or more, and may be 99.9% or more. The luminosity-corrected polarization degree Py of the polarizer may be 99.99% or less. The luminosity-corrected polarization degree Py can be calculated by performing luminosity correction on the obtained polarization degree using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) with a 2-degree visual field (C light source) according to "JIS Z 8701".
[0029] Increasing the luminosity-corrected polarization degree Py of the polarizer is advantageous in terms of improving the function of the optical laminate as an antireflection film and the durability of the optical laminate. If the luminosity-corrected polarization degree Py of the polarizer is less than 95%, the polarizer may not function as an antireflection film.
[0030] The thickness of the polarizer is 15 μm or less, preferably 13 μm or less, more preferably 10 μm or less. When the thickness of the polarizer is within this range, it is advantageous for thinning the optical laminate, and the retardation change amount can be more effectively suppressed. The thickness of the polarizer is usually 2 μm or more, preferably 3 μm or more, and may be, for example, 5 μm or more.
[0031] (3) First protective film The first protective film 21 has a function of protecting the surface of the polarizer 22. The first protective film 21 may be laminated in direct contact with the surface of the polarizer 22, or may be laminated via a pressure-sensitive adhesive layer in the linear polarizer. The first protective film 21 may be subjected to a surface treatment (e.g., corona treatment, etc.) in order to improve adhesion to the polarizer 22, and may have a thin layer such as a primer layer (also referred to as an easy-adhesion layer) formed thereon.
[0032] The thickness T1 of the first protective film is usually 60 μm or less, and from the viewpoint of suppressing curling of the entire polarizing plate under a durable environment, it is preferably 50 μm or less, more preferably 40 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.
[0033] As the first protective film, for example, a resin film having excellent transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, stretchability, etc. can be used. The resin film may be a thermoplastic resin film. Specific examples of such thermoplastic resins include: Cellulose ester resins such as triacetyl cellulose; Polyester resins such as polyethylene terephthalate and polyethylene naphthalate; Polyethersulfone resin; Polysulfone resin; Polycarbonate-based resins; Polyamide resins such as nylon and aromatic polyamides; Polyimide resin; Linear polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; Cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene resins); (Meth)acrylic resins such as polymethyl methacrylate; Polyarylate resins; Polystyrene resin; Polyvinyl alcohol resin, As well as mixtures thereof. The protective film made of the above thermoplastic resin may be commercially available.
[0034] Examples of linear polyolefin resins include linear olefin homopolymers such as polyethylene resins (polyethylene resins which are homopolymers of ethylene, and copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins which are homopolymers of propylene, and copolymers mainly composed of propylene), as well as copolymers composed of two or more types of linear olefins.
[0035] Cyclic polyolefin resin is a general term for resins polymerized with cyclic olefin as a polymerization unit, and examples thereof include resins described in JP-A-1-240517, JP-A-3-14882, JP-A-3-122137, etc. Specific examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers (typically random copolymers) of cyclic olefins and chain olefins such as ethylene and propylene, and graft polymers modified with unsaturated carboxylic acids or derivatives thereof, as well as hydrogenated products thereof. Among these, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers as cyclic olefins are preferably used.
[0036] The polyester resin is a resin having an ester bond in the main chain, and is generally a polycondensate of a polyvalent carboxylic acid or its derivative and a polyhydric alcohol. As the polyvalent carboxylic acid or its derivative, a divalent dicarboxylic acid or its derivative can be used, such as terephthalic acid, isophthalic acid, dimethyl terephthalate, dimethyl naphthalenedicarboxylate, etc. As the polyhydric alcohol, a divalent diol can be used, such as ethylene glycol, propanediol, butanediol, neopentyl glycol, cyclohexanedimethanol, etc. A representative example of the polyester resin is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol.
[0037] The cellulose ester resin is an ester of cellulose and fatty acid. Specific examples of the cellulose ester resin include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers having a plurality of polymerization units constituting these cellulose ester resins and those in which a part of hydroxyl groups is modified with other substituents are also included. Among these, cellulose triacetate (triacetyl cellulose) is particularly preferred.
[0038] The (meth)acrylic resin is a resin whose main constituent monomer is a compound having a (meth)acryloyl group. Specific examples of the (meth)acrylic resin include poly(meth)acrylic acid ester such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (MS resin, etc.); copolymers of methyl methacrylate and compounds having alicyclic hydrocarbon groups (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.). Preferably, a polymer whose main component is poly(meth)acrylic acid C1-C6 alkyl ester such as polymethyl (meth)acrylate is used, and more preferably, a methyl methacrylate resin whose main component is methyl methacrylate (50 to 100 mass%, preferably 70 to 100 mass%) is used.
[0039] The polycarbonate-based resin is composed of a polymer in which monomer units are bonded via carbonate groups. The polycarbonate-based resin may be a resin called a modified polycarbonate in which the polymer skeleton is modified, or a copolymer polycarbonate.
[0040] The first protective film may be a film containing the thermoplastic resin that has been stretched. Examples of stretching treatment include uniaxial stretching and biaxial stretching. Examples of stretching directions include the machine direction (MD) of the unstretched film, a direction perpendicular thereto (TD), and a direction oblique to the machine direction (MD). The biaxial stretching may be simultaneous biaxial stretching in which the film is stretched in two stretching directions at the same time, or sequential biaxial stretching in which the film is stretched in a predetermined direction and then stretched in the other direction. The stretching treatment may be performed, for example, by using two or more pairs of nip rolls with a high peripheral speed at the outlet side to stretch the film in the longitudinal direction (machine direction: MD), or by gripping both side ends of the unstretched film with chucks to spread it in the direction perpendicular to the machine direction (TD). At this time, the retardation value and the wavelength dispersion value can be controlled by adjusting the thickness of the film or the stretching ratio. In addition, the wavelength dispersion value can be controlled by adding a wavelength dispersion regulator to the resin.
[0041] The first protective film may contain any suitable additive depending on the purpose. Examples of the additive include antioxidants such as hindered phenols, phosphorus, and sulfur, stabilizers such as light stabilizers, ultraviolet absorbers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic and inorganic fillers; resin modifiers; plasticizers; lubricants; and retardation reducers. The types, combinations, and contents of the additives contained may be appropriately set depending on the purpose and desired properties.
[0042] In addition, in order to impart desired surface optical properties or other characteristics, a coating layer (surface treatment layer) may be provided on the outer surface of the first protective film. Specific examples of the surface treatment layer include a hard coat layer, an antiglare layer, an antireflection layer, an antistatic layer, and an antifouling layer. The method for forming the surface treatment layer is not particularly limited, and a known method can be used. The surface treatment layer may be formed on one surface or both surfaces of the first protective film.
[0043] The hard coat layer has a function of increasing the surface hardness of the first protective film, and is provided for the purpose of preventing surface scratches, etc. The hard coat layer preferably has a pencil hardness of H or harder, as measured by a pencil hardness test (measured by placing a protective film having a hard coat layer on a glass plate) specified in JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)".
[0044] The material for forming the hard coat layer is generally cured by heat or light. For example, organic hard coat materials such as organic silicone, melamine, epoxy, (meth)acrylic, and urethane (meth)acrylate, and inorganic hard coat materials such as silicon dioxide can be mentioned. Among these, urethane (meth)acrylate or polyfunctional (meth)acrylate hard coat materials are preferably used because they have good adhesion to the protective film and are excellent in productivity.
[0045] If desired, the hard coat layer may contain various fillers for the purpose of adjusting the refractive index, improving the flexural modulus, stabilizing the volume shrinkage rate, and further improving heat resistance, antistatic properties, antiglare properties, etc. The hard coat layer may also contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, leveling agents, and defoamers.
[0046] The hard coat layer may contain an additive to further improve its strength. The additive is not limited, and examples thereof include inorganic fine particles, organic fine particles, and mixtures thereof. The thickness of the hard coat layer is preferably thicker in order to provide hardness, but if it is too thick, it is likely to break when cut, so it may be 1 μm to 20 μm, or 2 μm to 10 μm. The thickness of the hard coat layer is preferably 3 μm to 7 μm.
[0047] The antiglare layer is a layer having a fine uneven surface, and is preferably formed using the above-mentioned hard coat material.
[0048] An anti-glare layer having a finely uneven surface can be formed by, for example, 1) forming a coating film containing fine particles on a protective film and providing unevenness based on the fine particles, or 2) forming a coating film, which may or may not contain fine particles, on a protective film, and then pressing the film against a mold (such as a roll) that has been given an uneven surface to transfer the uneven surface (also known as an embossing method).
[0049] The anti-reflection layer is a layer for weakening the reflection of external light on the surface of the protective film for a person observing the protective film, and usually has a reflectance of 1.5% or less for visible light. An anti-reflection layer with such a reflectance is typically formed by laminating a high refractive index layer having a high refractive index and a low refractive index layer having a low refractive index, or by using the method and materials described in JP 2021-6929 A. By adjusting these refractive indices and the thickness of each layer, the reflected light from each layer can be weakened by each other, and excellent anti-reflection function is achieved.
[0050] As described in detail later, it is preferable to manufacture the antireflection layer consisting of a high refractive index layer and a low refractive index layer using a coating composition capable of forming each of the high refractive index layer and the low refractive index layer, since the operation is extremely simple. Here, an example of a coating composition capable of forming each of the high refractive index layer and the low refractive index layer will be given. Such a coating composition is liquid and contains an appropriate curable resin and, if necessary, an additive. A coating composition capable of forming a high refractive index layer (a composition for forming a high refractive index layer) is, for example, a curable resin such as urethane acrylate, and an initiator (photopolymerization initiator) for photopolymerization such as acetophenone, benzophenone, benzyl dimethyl ketal, α-hydroxyalkylphenone, α-aminoalkylphenone, or thioxanthone, dissolved in a solvent such as methyl ethyl ketone or methyl isobutyl ketone. In order to improve the coating property, a leveling agent, preferably a fluorine-based leveling agent, may be included. In addition, as a coating composition capable of forming a low refractive index layer (composition for forming a low refractive index layer), a binder resin such as polyethylene glycol diacrylate or pentaerythritol (tri / tetra)acrylate as a curable resin is used, and an initiator for photopolymerization (photopolymerization initiator) such as acetophenone, benzophenone, benzyl dimethyl ketal, α-hydroxyalkylphenone, α-aminoalkylphenone, or thioxanthone is dissolved in a solvent such as 1-methoxy-2-propyl acetate or methyl isobutyl, and silica particles are dispersed in the solution. In order to improve the coating property, a fluorine-based leveling agent may be included. Note that the coating compositions capable of forming the high refractive index layer and the low refractive index layer listed here are merely examples, and it is preferable to optimize the composition for forming a high refractive index layer and the composition for forming a low refractive index layer, respectively, depending on the characteristics of the antireflection layer to be formed.
[0051] The antireflection layer may, for example, include a low refractive index layer, or may have a multi-layer structure further including a high refractive index layer and / or a medium refractive index layer between the protective film and the low refractive index layer.
[0052] The low refractive index layer can be formed by applying a coating liquid containing a cured product of the above-mentioned curable resin, a light-transmitting resin such as a metal alkoxide polymer, and inorganic particles, and then curing the coating layer as necessary. Examples of inorganic particles include low refractive index particles such as LiF (refractive index 1.4), MgF (refractive index 1.4), 3NaF·AlF (refractive index 1.4), AlF (refractive index 1.4), and Na3AlF6 (refractive index 1.33), and hollow silica particles.
[0053] The antistatic layer is provided for the purpose of imparting electrical conductivity to the surface of the first protective film and suppressing the effects of static electricity. For example, the antistatic layer can be formed by applying a resin composition containing an electrically conductive substance (antistatic agent) onto the first protective film. For example, an antistatic hard coat layer can be formed by adding an antistatic agent to the hard coat material used to form the hard coat layer described above.
[0054] The antifouling layer is provided to impart water repellency, oil repellency, sweat resistance, antifouling properties, etc. A suitable material for forming the antifouling layer is a fluorine-containing organic compound. Examples of the fluorine-containing organic compound include fluorocarbon, perfluorosilane, and polymeric compounds thereof. The method for forming the antifouling layer can be a physical vapor deposition method, typically vapor deposition or sputtering, a chemical vapor deposition method, a wet coating method, or the like, depending on the material to be formed. The average thickness of the antifouling layer is usually about 1 to 50 nm, and preferably 3 to 35 nm.
[0055] When the optical laminate is applied to an image display device, diffusion of the dichroic dye such as iodine in the polarizer 22 may cause corrosion of metal members (electrodes, etc.) present in the vicinity of the optical laminate in the image display device. This is because the dichroic dye such as iodine migrates to the metal members due to the diffusion. In order to suppress corrosion of the metal members, it is preferable to suppress the amount of the dichroic dye migrating to the metal members.
[0056] The moisture permeability of the first protective film is 100g / (m 2·day) or more. This moisture permeability is preferably 100g / (m 2 ·day) or more 2000g / (m 2 ·day) or less, and 200g / (m 2 ·day) or more 1000g / (m 2 ·day) or less is more preferable, and 300g / (m 2 ·day) or more 500g / (m 2 ·day) or less. When iodine contained in the polarizer migrates between the layers of the optical laminate 1, if the moisture permeability of the first protective film 21 is too low, the migration of iodine is too suppressed and tends to be biased toward the opposite direction (toward the retarder side). Also, if the moisture permeability of the first protective film 21 is too high, the polarizer tends to be easily deteriorated by moist heat. Therefore, it is preferable that the moisture permeability of the first protective film is appropriately high so that when iodine migrates toward the first protective film 21 side, the iodine passes through the first protective film 21 and diffuses out of the optical laminate 1.
[0057] (4) Second protective film The second protective film 23 has a function of protecting the surface of the polarizer 22. The second protective film 23 may be laminated in direct contact with the surface of the polarizer 22, or may be laminated via a pressure-sensitive adhesive layer in the linear polarizer. The second protective film 23 may be subjected to a surface treatment (e.g., corona treatment, etc.) in order to improve adhesion to the polarizer 22, and may have a thin layer such as a primer layer (also referred to as an easy-adhesion layer) formed thereon.
[0058] The moisture permeability of the second protective film 23 is 1200 g / (m 2 ·day) or less. This moisture permeability is 0.1g / (m 2 ·day) or more 800g / (m 2 ·day) or less, and 0.5g / (m 2 ·day) or more 500g / (m 2 ·day) or less is more preferable, and 1g / (m 2 ·day) or more than 100g / (m 2 ·day) or less, and more preferably 10 g / (m2 ·day) or more than 50g / (m 2 ·day) or less. When the moisture permeability of the second protective film 23 is within this range, it is possible to sufficiently prevent iodine from migrating to the phase shifter side. In addition, it is particularly preferable that the moisture permeability of the second protective film 23 is 10 g / (m 2 ·day) is also preferable from the viewpoint of Δα, which will be described later. The moisture permeability of the second protective film 23 can be measured according to the description in the [Example] section.
[0059] The thickness T2 of the second protective film is, for example, 0.1 to 60 μm, preferably 0.2 to 30 μm. It is advantageous for this embodiment that the thickness T2 of the second protective film is appropriately thin. That is, when the antistatic agent contained in the pressure-sensitive adhesive layer described later moves between layers of the optical laminate 1, if the thickness of the second protective film 23 is too large, the movement of the antistatic agent is too much suppressed and tends to be biased toward the opposite direction (toward the image display panel). Therefore, from the viewpoint of suppressing corrosion of the metal member, the thickness T2 of the second protective film is preferably 1 to 10 μm, more preferably 2 to 8 μm, and even more preferably 3 to 5 μm.
[0060] As the second protective film, for example, a resin film having excellent transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, stretchability, etc. can be used. The resin film may be a thermoplastic resin film. Specific examples of such thermoplastic resins are the same as those described for the first protective film. The protective film made of a thermoplastic resin may be available on the market.
[0061] The thermoplastic resin constituting the thermoplastic resin film used as the second protective film and the thermoplastic resin layer described below is preferably a cyclic polyolefin-based resin, a polyester-based resin, a polycarbonate-based resin, a (meth)acrylic resin, or a polystyrene-based resin, more preferably a cyclic polyolefin-based resin, a (meth)acrylic resin, or a polystyrene-based resin, even more preferably a cyclic polyolefin-based resin or a (meth)acrylic resin, and even more preferably a cyclic polyolefin-based resin.
[0062] The thermoplastic resin film used as the second protective film may be a film existing alone, and in this case, the thermoplastic resin film is laminated on the polarizer 22 via a pressure-sensitive adhesive layer in the linear polarizer as necessary. Alternatively, the second protective film may be a thermoplastic resin layer. For example, a composition containing a thermoplastic resin is applied onto a supporting substrate, and dried as necessary to obtain a thermoplastic resin layer with a supporting substrate. The thermoplastic resin layer is attached to the polarizer 22 via a pressure-sensitive adhesive layer in the linear polarizer as necessary, and then the supporting substrate is peeled off and removed, thereby laminating a thermoplastic resin layer as the second protective film on the polarizer 22 (first method).
[0063] When the second protective film is a thermoplastic resin layer, it is also possible to form a thermoplastic resin layer by directly applying the composition to the surface of the polarizer 22 and drying it as necessary (second method). However, when the composition contains a solvent, the first method is preferred because it is easier to stably form a thermoplastic resin layer with a sufficiently reduced solvent content.
[0064] The second protective film may be a cured resin layer containing a cured product of a curable resin. Examples of the curable resin include thermosetting resins and active energy curable resins, such as (meth)acrylic resins, epoxy resins, oxetane resins, urethane resins, (meth)acrylic urethane resins, and melamine resins. The cured resin layer containing a cured product of a curable resin can be formed by applying a composition containing a curable resin onto a support substrate, drying the composition as necessary, and then applying heat or irradiating the composition with active energy rays such as visible light, ultraviolet light, infrared light, X-rays, α rays, β rays, γ rays, and electron beams. The obtained cured resin layer with a support substrate is attached to the polarizer 22 via a pressure-sensitive adhesive layer in a linear polarizing plate as necessary, and then the support substrate is peeled off and removed, thereby laminating a cured resin layer as a second protective film on the polarizer 22.
[0065] From the viewpoint of moisture permeability or suppressing a change in retardation properties, the second protective film is preferably a thermoplastic resin film or layer made of a cyclic polyolefin resin, a thermoplastic resin film or layer made of a (meth)acrylic resin, a cured resin layer containing a cured product of a (meth)acrylic resin, or a thermoplastic resin film or layer made of a polystyrene resin. In consideration of further suppressing migration of the dichroic dye in the polarizer 22 to the metal member, the second protective film is more preferably a thermoplastic resin film or layer made of a cyclic polyolefin resin, or a thermoplastic resin film or layer made of a polystyrene resin.
[0066] The second protective film may contain any suitable additive depending on the purpose. Specific examples of the additive are the same as those described for the first protective film.
[0067] The second protective film preferably has no retardation properties or has a small retardation value. Specifically, the second protective film preferably has an in-plane retardation value of 10 nm or less at a wavelength of 550 nm. The in-plane retardation value is 0 nm or more. The second protective film preferably has a thickness direction retardation value of -10 nm to +10 nm at a wavelength of 550 nm.
[0068] (5) Phaser The retarder 4 is an optical element exhibiting retardation in the in-plane or thickness direction, and preferably includes a retardation film. The retardation film is a film exhibiting retardation in the in-plane or thickness direction, and is a layer (cured layer) made of a polymer of a polymerizable liquid crystal compound, or a combination of the layer and an alignment film. The retardation film includes, for example, a cured layer of a retardation film-forming composition containing a polymerizable liquid crystal compound.
[0069] When the retarder 4 includes a retardation film, the dichroic dye migrates to the metal member, which easily causes the above-mentioned corrosion of the metal member, but according to the present invention, the above-mentioned corrosion can be effectively suppressed even when the retarder 4 includes a retardation film. Furthermore, when the retarder 4 includes a retardation film, this is advantageous for making the optical laminate thinner, and when the retarder 4 includes a retardation film, this is preferable in that the wavelength dispersion characteristics can be arbitrarily designed.
[0070] The retarder 4 in the optical laminate 1 of this embodiment has two types of retardation films (hereinafter also referred to as "retardation layers"). That is, a first retardation layer 41 and a second retardation layer 43 are laminated with an inner retarder pressure-sensitive adhesive layer 42. In this specification, the retardation films included in the retarder 4 may be referred to as the "first retardation layer" and the "second retardation layer" in the order of proximity to the linear polarizer 2. Hereinafter, possible configurations of the retarder 4 will be described.
[0071] (5-1) Retardation film The retardation film is usually formed by applying a retardation film-forming composition onto an alignment film formed on a substrate, and polymerizing the polymerizable liquid crystal compound contained in the retardation film-forming composition. The retardation film is usually a film in which the polymerizable liquid crystal compound is cured in an aligned state, and in order to generate a retardation in the viewing surface, it is necessary to be a cured film in which the polymerizable group is polymerized in a state in which the polymerizable liquid crystal compound is aligned horizontally relative to the substrate surface. In this case, if the polymerizable liquid crystal compound is a rod-shaped liquid crystal, a positive A plate is sufficient, and if the polymerizable liquid crystal compound is a disc-shaped liquid crystal, a negative A plate is sufficient.
[0072] The retarder may include two or more retardation films having different optical anisotropy. In order to achieve a high degree of anti-reflection function, it is sufficient to have a λ / 4 plate function (i.e., a π / 2 phase difference function) in the entire visible light range. Specifically, a reverse wavelength dispersion λ / 4 retardation layer is preferable, or it is preferable to combine two or more retardation films with different orientations. For example, a retardation film having a λ / 2 plate function (i.e., a π phase difference function) and a retardation film having a λ / 4 plate function (i.e., a π / 2 phase difference function) may be combined. Furthermore, from the viewpoint of compensating for the anti-reflection function in an oblique direction, it is preferable to further include a layer (positive C plate) having anisotropy in the thickness direction. In particular, when the retarder includes a reverse wavelength dispersion λ / 4 retardation layer and a positive C plate, the effect of the present invention can be obtained more remarkably. In addition, each retardation film may have a tilt orientation or may form a cholesteric orientation state.
[0073] When two or more types of retardation films having different retarder orientations are laminated together, they can be laminated via the retarder internal pressure-sensitive adhesive layer 42. From the viewpoint of suppressing corrosion of metal members included in the image display panel to which the optical laminate is laminated, the retarder internal pressure-sensitive adhesive layer 42 is preferably an adhesive layer having low moisture permeability.
[0074] In the optical laminate 1, iodine contained in the polarizer 22 and an antistatic agent contained in the pressure-sensitive adhesive layer 5 described below can migrate between layers and transfer to the retarder. In this case, when the retardation film is made of a polymerizable liquid crystal compound, the retardation characteristics change (for example, increase) due to the influence of iodine and the antistatic agent. From this viewpoint, the water vapor transmission coefficient of the retarder is preferably 100 or less. This water vapor transmission coefficient is preferably 1 or more and 75 or less, more preferably 5 or more and 50 or less, and even more preferably 10 or more and 35 or less. Here, the "water vapor transmission coefficient" is the moisture permeability (unit: g / (m)) of the retarder at 65°C. 2 It means a value expressed by the product of the number of days (days) and the thickness (unit: mm). When iodine or antistatic agent moves between layers of the optical laminate 1, if the water vapor permeability coefficient of the phase shifter 4 is too high, the movement of iodine and antistatic agent increases, and the degree of suppression of the phase difference change of the first phase difference layer or the second phase difference layer, which should suppress the phase difference change, and the effect of suppressing corrosion of the metal member tend to be lower than the original suppression effect. In addition, if the water vapor permeability coefficient is too low, the antistatic agent becomes excessively difficult to permeate, and the antistatic agent tends to move toward the metal member. Therefore, it is preferable that the water vapor permeability coefficient of the phase shifter is moderately low.
[0075] The λ / 4 function of the retarder over the entire visible light range preferably satisfies the optical characteristics shown in the following formula (1), where Re(λ) is the in-plane retardation value for light with a wavelength of λ nm, and more preferably satisfies the optical characteristics shown in the following formulas (1), (2), and (3). The in-plane retardation value Re(λ) of the retarder is a value measured by laminating a linear polarizer and a retarder in this order using a retardation measuring device (KOBRA-WPR, manufactured by Oji Scientific Instruments Co., Ltd.). 100nm <Re(550)<160nm (1) (In the formula, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.) Re(450) / Re(550)≦1.0 (2) 1.00≦Re(650) / Re(550) (3) (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.)
[0076] The wavelength dispersion α of the retarder is preferably within a predetermined range. Here, the "wavelength dispersion α" is the ratio (Re(450) / Re(550)) of the in-plane retardation value Re(450) at a wavelength of 450 nm to the in-plane retardation value Re(550) at a wavelength of 550 nm. Since the reverse wavelength dispersion property is improved and the optical properties of the optical laminate are further improved, the wavelength dispersion α is preferably 0.70 or more, more preferably 0.78 or more. For the same reason, the wavelength dispersion α is preferably 0.92 or less, more preferably 0.90 or less, even more preferably 0.88 or less, and particularly preferably 0.87 or less. The value of "Re(450) / Re(550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound, the lamination angle of the multiple retardation films, and the retardation value.
[0077] The in-plane retardation value of the retardation film can be adjusted by the thickness of the retardation film. Since the in-plane retardation value is determined by the following formula (4), a desired in-plane retardation value (Re(λ)) can be obtained by adjusting Δn(λ) and the thickness d. The thickness of the retardation film is preferably 0.5 μm to 5 μm, more preferably 1 μm to 3 μm. The thickness of the retardation film can be measured by an interference thickness meter, a laser microscope, or a stylus thickness meter. Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound described later. Re(λ)=d×Δn(λ) (4) (In the formula, Re(λ) represents an in-plane retardation value at a wavelength of λ nm, d represents a thickness, and Δn(λ) represents a birefringence at a wavelength of λ nm.)
[0078] The positive C plate is not particularly limited as long as it has anisotropy in the thickness direction, but if it does not have tilt alignment or cholesteric alignment, it has the optical characteristics expressed by formula (5). nx≒ny <nz (5)
[0079] The in-plane retardation value Re(550) of the positive C plate at a wavelength of 550 nm is usually in the range of 0 to 10 nm, preferably in the range of 0 to 5 nm. The retardation value Rth(550) in the thickness direction at a wavelength of 550 nm is usually in the range of -170 nm or more and -10 nm or less, preferably in the range of -150 nm or more and -20 nm or less, more preferably in the range of -100 nm or more and -40 nm or less. If the retardation value in the thickness direction is in this range, the anti-reflection property from an oblique direction can be further improved.
[0080] The polymerizable liquid crystal compound contained in the retardation film forming composition means a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group, and as the polymerizable liquid crystal compound, a conventionally known polymerizable liquid crystal compound can be used. The photopolymerizable group means a group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound may be either rod-shaped or discotic. The polymerizable liquid crystal compound may be used alone or in combination of two or more kinds.
[0081] As the polymerizable liquid crystal compound, from the viewpoint of expressing reverse wavelength dispersion, a liquid crystal having a T-shaped or H-shaped mesogen structure further having birefringence in a direction perpendicular to the molecular long axis direction is preferable, and from the viewpoint of obtaining stronger dispersion, a T-shaped liquid crystal is more preferable. Specific examples of the structure of the T-shaped liquid crystal include those represented by the following formula (I): [ka] Examples of the compound include compounds represented by the following formula:
[0082] In formula (I), Ar represents a divalent aromatic group which may have a substituent. The divalent aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a divalent bonding group such as a single bond, -CO-O-, or -O-. G 1 and G 2 each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. L 1 , L 2 , B 1 and B. 2 each independently represents a single bond or a divalent linking group. k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, B 1 and B. 2 , G 1 and G 2 may be the same as or different from each other. E 1 and E 2 each independently represents an alkanediyl group having 1 to 17 carbon atoms, in which a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S-, or -COO-, and when there are a plurality of -O-, -S-, or -COO-, they are not adjacent to each other. 1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0083] G 1 and G 2 are each independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 Or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.
[0084] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, R a7 OC=OOR a8 -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1-, -CH2-, -CH2CH2-, -COOR a4-1 - or OCOR a6-1 -, where R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.
[0085] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 O.C.O.R. a14 - or R a15 OC=OOR a16 -, where R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B. 2 are each independently preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 - or OCOR a14-1 -, where R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. B 1 and B. 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0086] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is preferable.
[0087] E 1 and E 2 are each independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.
[0088] P 1 Or P 2 Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.
[0089] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable that Ar has a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable that Ar has a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has a π electron.
[0090] In formula (I), the total number of π electrons contained in the divalent aromatic group represented by Ar is N πis preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0091] Suitable examples of the aromatic group represented by Ar include the following groups:
[0092] [ka]
[0093] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0094] Q 1 , Q 2 and Q 3 are each independently -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ represents -, -CO- or O-; R 2’ and R 3’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0095] J 1 , and J 2 each independently represents a carbon atom or a nitrogen atom.
[0096] Y 1 , Y2 and Y 3 each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.
[0097] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.
[0098] Y 1 , Y 2 and Y 3 Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.
[0099] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0100] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; 1 and Z 2is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group.
[0101] Q 1 , Q 2 and Q 3 -NH-, -S-, -NR 2’ -, -O- are preferred, R 2’ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable.
[0102] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability. In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.
[0103] Among the polymerizable liquid crystal compounds, compounds having a maximum absorption wavelength of 300 to 400 nm are preferred. When the polymerizable liquid crystal composition contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the polymerizable liquid crystal compound has a maximum absorption wavelength of 300 to 400 nm, even if the polymerizable liquid crystal composition is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it is advantageous in terms of long-term stability of the polymerizable liquid crystal composition, and the alignment property and thickness uniformity of the obtained retardation film can be improved. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and examples thereof include chloroform and the like.
[0104] An example of the discotic polymerizable liquid crystal compound is a compound containing a group represented by formula (W) (hereinafter, also referred to as "polymerizable liquid crystal compound (W)"). [ka] [In formula (W), R 40 represents the following formulas (W-1) to (W-5). [ka] [In formulas (W-1) to (W-5), X 40 and Z 40 each independently represents an alkanediyl group having 1 to 12 carbon atoms, a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-. m2 represents an integer.
[0105] Examples of the rod-shaped polymerizable liquid crystal compound include compounds represented by formula (II), formula (III), formula (IV), formula (V), formula (VI) or formula (VII). P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (II) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (III) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (IV) P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (V) P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (VI) P11-B11-E11-B12-A11-B13-A12-F11 (VII) [In formulas (II) to (VII), A11 to A14 each independently represent a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group, and a hydrogen atom contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom. B11 and B17 each independently represent -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, or -CO-NR 16 -, -NR 16 R represents -CO-, -CO-, -CS-, or a single bond. 16 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. B12 to B16 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR16 It represents -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond. E11 and E12 each independently represent an alkanediyl group having 1 to 12 carbon atoms, and a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-. F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxy group, a methylol group, a formyl group, a sulfo group (-SO3H), a carboxy group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-. P11 and P12 each independently represent a polymerizable group.]
[0106] The content of the polymerizable liquid crystal compound in the retardation film forming composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, based on 100 parts by mass of the solid content of the retardation film forming composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the alignment of the obtained retardation film. In this specification, the solid content of the polymerizable liquid crystal composition means all components excluding volatile components such as organic solvents from the polymerizable liquid crystal composition.
[0107] (5-2) Composition for forming retardation film As described above, the retardation film forming composition contains a polymerizable liquid crystal compound. The retardation film forming composition may further contain reactive additives such as a solvent, a leveling agent, a polymerization initiator, a photosensitizer, a polymerization inhibitor, a crosslinking agent, and an adhesive agent, and it is preferable to contain a solvent and a leveling agent from the viewpoint of processability.
[0108] The retardation film forming composition may contain a solvent. Generally, the polymerizable liquid crystal compound has a high viscosity, so that the retardation film forming composition dissolved in a solvent is easy to apply, and as a result, the retardation film is often easy to form. The solvent is preferably one that can completely dissolve the polymerizable liquid crystal compound, and is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound.
[0109] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone. These solvents may be used alone or in combination of two or more.
[0110] The content of the solvent is preferably 50 to 98% by mass based on the total amount of the composition for forming a retardation film. In other words, the content of the solid content in the composition for forming a retardation film is preferably 2 to 50% by mass, more preferably 5 to 30% by mass. When the content of the solid content is 50% by mass or less, the viscosity of the composition for forming a retardation film is low, and the thickness of the retardation film becomes approximately uniform, so that the retardation film tends to be less prone to unevenness. In addition, the content of the solid content can be determined in consideration of the thickness of the retardation film to be produced.
[0111] The retardation film forming composition may contain a leveling agent. The leveling agent is an additive that adjusts the fluidity of the composition and makes the film obtained by applying the composition flatter, and examples of the leveling agent include organic modified silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents. Among them, when horizontal alignment is performed, polyacrylate-based and perfluoroalkyl-based leveling agents are preferred, and when vertical alignment is performed, organic modified silicone-based and perfluoroalkyl-based leveling agents are preferred.
[0112] When the composition for forming a retardation film contains a leveling agent, the content is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned horizontally, and the obtained retardation film tends to be smoother. When the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, the obtained retardation film tends to be easily uneven. The composition for forming a retardation film may contain two or more kinds of leveling agents.
[0113] The retardation film-forming composition may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferable from the viewpoint of not depending on the phase state of the thermotropic liquid crystal.
[0114] The photopolymerization initiator can be any known photopolymerization initiator as long as it is a compound capable of initiating the polymerization reaction of the polymerizable liquid crystal compound.Specific examples of the photopolymerization initiator include photopolymerization initiators capable of generating active radicals or acids by the action of light, and among these, photopolymerization initiators that generate radicals by the action of light are preferred.The photopolymerization initiators can be used alone or in combination of two or more kinds.
[0115] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates an active radical, a self-cleavage type benzoin compound, acetophenone compound, hydroxyacetophenone compound, α-aminoacetophenone compound, oxime ester compound, acylphosphine oxide compound, azo compound, etc. can be used, and a hydrogen abstraction type benzophenone compound, alkylphenone compound, benzoin ether compound, benzyl ketal compound, dibenzosuberone compound, anthraquinone compound, xanthone compound, thioxanthone compound, halogenoacetophenone compound, dialkoxyacetophenone compound, halogenobisimidazole compound, halogenotriazine compound, triazine compound, etc. can be used. As a photopolymerization initiator that generates an acid, an iodonium salt and a sulfonium salt can be used. From the viewpoint of excellent reaction efficiency at low temperatures, self-cleavage type photopolymerization initiators are preferred, and in particular, acetophenone-based compounds, hydroxyacetophenone-based compounds, α-aminoacetophenone-based compounds, and oxime ester-based compounds are preferred.
[0116] The content of the polymerization initiator in the retardation film-forming composition can be appropriately adjusted depending on the type and amount of the polymerizable liquid crystal compound, but is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0117] The retardation film forming composition may contain a sensitizer. The sensitizer is preferably a photosensitizer. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and an alkoxy group-containing anthracene (e.g., dibutoxyanthracene, etc.); phenothiazine, rubrene, etc.
[0118] When the retardation film-forming composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the retardation film-forming composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0119] In order to stably proceed with the polymerization reaction, the retardation film-forming composition may contain an antioxidant, which can control the degree of progress of the polymerization reaction of the polymerizable liquid crystal compound.
[0120] The antioxidant may be, for example, a primary antioxidant selected from a phenol-based antioxidant, an amine-based antioxidant, a quinone-based antioxidant, or a nitroso-based antioxidant, or a secondary antioxidant selected from a phosphorus-based antioxidant and a sulfur-based antioxidant.
[0121] When the retardation film forming composition contains an antioxidant, the content of the antioxidant is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. The antioxidants can be used alone or in combination of two or more kinds. When the content of the antioxidant is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0122] The retardation film forming composition may contain a reactive additive. The reactive additive preferably has a carbon-carbon unsaturated bond, an active hydrogen reactive group, or a thiol group in its molecule. The "active hydrogen reactive group" here means a group reactive to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), or an amino group (-NH2), and representative examples thereof include a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group. The number of reactive groups possessed by the reactive additive is usually 1 to 20, and preferably 1 to 10.
[0123] (5-3) Base material The above-mentioned substrate for forming the retardation film includes glass substrate and film substrate, and film substrate is preferred, and long roll-shaped film is more preferred in terms of continuous production.The resin constituting the film substrate includes, for example, linear polyolefin such as polyethylene and polypropylene; cyclic olefin resin; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid ester; polyacrylic acid ester; cellulose ester such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene oxide; and the like.Among them, from the viewpoint of transparency when used for optical film applications, a film substrate selected from any of triacetyl cellulose, cyclic olefin resin, polymethacrylic acid ester, and polyethylene terephthalate is more preferred.
[0124] Examples of commercially available cellulose ester substrates include "FUJITAC FILM" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (all manufactured by Konica Minolta Opto Co., Ltd.). Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona (Germany)), "ARTON" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (all manufactured by Zeon Corporation) and "Apel" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be formed into a film by known means such as a solvent casting method or a melt extrusion method to form a substrate. Commercially available cyclic olefin resin substrates can also be used. Commercially available cyclic olefin resin substrates include "S-Cina" (registered trademark), "SCA40" (registered trademark) (both manufactured by Sekisui Chemical Co., Ltd.), "ZEONORFILM" (registered trademark) (manufactured by Optes Co., Ltd.), and "ARTONFILM" (registered trademark) (manufactured by JSR Corporation).
[0125] The thickness of the substrate is preferably thin enough to be practically handled, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the substrate is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 to 50 μm. In addition, by peeling off the substrate and transferring the retardation film, a further thinning effect can be obtained.
[0126] (5-4) Alignment film In this specification, the alignment film has an alignment regulating force for aligning a polymerizable liquid crystal compound in a desired direction.
[0127] The alignment film facilitates the liquid crystal alignment of the polymerizable liquid crystal compound. The state of liquid crystal alignment, such as horizontal alignment, vertical alignment, hybrid alignment, and tilt alignment, varies depending on the properties of the alignment film and the polymerizable liquid crystal compound, and the combination can be selected arbitrarily. For example, if the alignment film is a material that exerts horizontal alignment as an alignment control force, the polymerizable liquid crystal compound can form a horizontal alignment or a hybrid alignment, and if the alignment film is a material that exerts vertical alignment, the polymerizable liquid crystal compound can form a vertical alignment or a tilt alignment. The expressions horizontal, vertical, and the like refer to the direction of the optical axis of the aligned polymerizable liquid crystal compound when the retardation film plane is used as a reference. For example, vertical alignment means that the optical axis of the aligned polymerizable liquid crystal compound is in a direction perpendicular to the retardation film plane. The term "vertical" here means 90°±20° relative to the retardation film plane.
[0128] When the alignment film is made of an alignment polymer, the alignment regulating force can be arbitrarily adjusted by the surface state or rubbing conditions, and when it is made of a photoalignment polymer, the alignment regulating force can be arbitrarily adjusted by the polarized light irradiation conditions, etc. In addition, the liquid crystal alignment can be controlled by selecting the physical properties, such as the surface tension and liquid crystallinity, of the polymerizable liquid crystal compound.
[0129] The alignment film formed between the substrate and the retardation film is preferably insoluble in the solvent used when forming the retardation film on the alignment film, and is heat-resistant in the heat treatment for removing the solvent and for aligning the liquid crystal. The alignment film may be an alignment film made of an orienting polymer, a photoalignment film, a groove alignment film, or a stretched film stretched in the alignment direction. When applied to a long rolled film, a photoalignment film is preferred because the alignment direction can be easily controlled.
[0130] The thickness of the alignment film is usually in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 to 300 nm.
[0131] Examples of the alignment polymer used in the rubbed alignment film include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and their hydrolyzates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. These alignment polymers may be used alone or in combination of two or more.
[0132] An example of a rubbing method is to bring an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to the substrate and annealing the composition into contact with a rotating rubbing roll wrapped with a rubbing cloth.
[0133] The photo-alignment film is made of a polymer, oligomer, or monomer having a photoreactive group. The photo-alignment film can obtain an alignment control force by irradiating it with polarized light. The photo-alignment film is more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0134] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it is a group that generates a photoreaction that is the origin of liquid crystal alignment ability, such as molecular alignment induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by irradiation with light. Among the photoreactive groups, those that cause a dimerization reaction or a photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group that can generate the above-mentioned reaction, those having an unsaturated bond, particularly a double bond, are preferred, and groups having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) are more preferred.
[0135] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. From the viewpoint of easy control of reactivity and expression of alignment control force during photoalignment, chalcone groups and cinnamoyl groups are preferred. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, and formazan groups, and groups having azoxybenzene as a basic structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0136] The polarized light may be irradiated directly from the film surface or from the substrate side and then transmitted. It is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. These lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated through an appropriate polarizer to irradiate the polarized light. As such a polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0137] (6)Adhesive layer The optical laminate 1 of this embodiment includes three types of adhesive layers (adhesive layer in the linear polarizer, adhesive layer 3 between the linear polarizer and the phase shifter, and adhesive layer in the phase shifter).
[0138] The adhesive layer in the linear polarizer (not shown in FIG. 1) is a layer provided as necessary as a component of the linear polarizer 2 for bonding the first protective film 21 and the polarizer 22 and for bonding the polarizer 22 and the second protective film 23. The optical laminate preferably includes both of these adhesive layers in the linear polarizer. The adhesive layer 3 between the linear polarizer and the phase shifter is a layer provided for bonding the linear polarizer 2 and the phase shifter 4. The optical laminate preferably includes the adhesive layer 3 between the linear polarizer and the phase shifter. The adhesive layer 42 in the phase shifter is a layer used for bonding the first retardation layer 41 (e.g., λ / 4 retardation layer) and the second retardation layer 43 (e.g., a positive C plate) in the phase shifter 4.
[0139] The adhesive layer in the linear polarizer, the adhesive layer 3 between the linear polarizer and the phaser, and the adhesive layer 42 in the phaser may be either an adhesive layer or an adhesive layer. The adhesive layer is a layer formed from an adhesive composition (pressure-sensitive adhesive composition), and the adhesive layer is a layer formed from an adhesive composition. The adhesive layer in the linear polarizer and the adhesive layer 42 in the phaser are preferably adhesive layers. In particular, the adhesive layer 42 in the phaser is preferably one having low moisture permeability from the viewpoint of suppressing the movement of the antistatic agent described later, and is therefore preferably made of an active energy ray curable adhesive. In addition, in order to suppress cracks in the phaser, an adhesive layer having a higher elastic modulus than the adhesive layer is preferred. On the other hand, the adhesive layer 3 between the linear polarizer and the phaser is preferably an adhesive layer.
[0140] (6-1) Adhesive layer Examples of the adhesive composition forming the adhesive layer include an aqueous adhesive composition, and a curable adhesive composition that is cured by heating or irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Examples of the aqueous adhesive composition include a composition in which a polyvinyl alcohol resin or a urethane resin is dissolved in water as the main component, and a composition in which a polyvinyl alcohol resin or a urethane resin is dispersed in water as the main component. The aqueous adhesive composition may further contain a curable component or a crosslinking agent such as a polyaldehyde, a melamine compound, a zirconia compound, a zinc compound, a glyoxal compound, or a water-soluble epoxy resin. Examples of the aqueous adhesive composition include the adhesive composition described in JP 2010-191389 A, the adhesive composition described in JP 2011-107686 A, the composition described in JP 2020-172088 A, and the composition described in JP 2005-208456 A.
[0141] The curable adhesive composition is preferably an active energy ray curable adhesive composition that contains a curable (polymerizable) compound as a main component and is cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive composition include a cationic polymerization type adhesive composition that contains a cationic polymerizable compound as a curable compound, a radical polymerization type adhesive composition that contains a radical polymerizable compound as a curable compound, and a hybrid type adhesive composition that contains both a cationic polymerizable compound and a radical polymerizable compound as a curable compound.
[0142] The cationic polymerizable compound is a compound or oligomer that undergoes cationic polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and specific examples thereof include epoxy compounds, oxetane compounds, vinyl compounds, etc. Examples of epoxy compounds include alicyclic epoxy compounds such as 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule); aromatic epoxy compounds such as diglycidyl ether of bisphenol A (compounds having an aromatic ring and an epoxy group in the molecule); and aliphatic epoxy compounds such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether (compounds having at least one oxirane ring bonded to an aliphatic carbon atom in the molecule).
[0143] Examples of the oxetane compound include compounds having one or more oxetane rings in the molecule, such as 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane.
[0144] The cationic polymerization adhesive composition preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a thermal cationic polymerization initiator or a photo-induced cationic polymerization initiator. Examples of the cationic polymerization initiator include aromatic diazonium salts such as benzenediazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyliodonium tetrakis(pentafluorophenyl)borate; aromatic sulfonium salts such as triphenylsulfonium hexafluorophosphate; and iron-arene complexes such as xylene-cyclopentadienyl iron(II) hexafluoroantimonate. The content of the cationic polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerizable compound. Two or more kinds of cationic polymerization initiators may be included.
[0145] Examples of cationic polymerization adhesive compositions include the cationic polymerizable compositions described in JP 2016-126345 A and JP 2021-113969 A.
[0146] The radical polymerizable compound is a compound or oligomer that undergoes a radical polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and specifically includes a compound having an ethylenically unsaturated bond. Examples of the compound having an ethylenically unsaturated bond include a (meth)acrylic compound having one or more (meth)acryloyl groups in the molecule, and a vinyl compound having one or more vinyl groups in the molecule.
[0147] Examples of the (meth)acrylic compound include (meth)acrylate monomers having at least one (meth)acryloyloxy group in the molecule, (meth)acrylamide monomers, and (meth)acryl group-containing compounds obtained by reacting two or more functional group-containing compounds and having at least two (meth)acryloyl groups in the molecule, such as (meth)acrylic oligomers.
[0148] The radical polymerization adhesive composition preferably contains a radical polymerization initiator. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator. Examples of the radical polymerization initiator include acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; xanthone, fluorenone, and the like. The content of the radical polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound. Two or more types of radical polymerization initiators may be included.
[0149] Examples of radical polymerization adhesive compositions include the radical polymerizable compositions described in JP 2016-126345 A, JP 2016-153474 A, and WO 2017 / 183335 A.
[0150] The active energy ray-curable adhesive composition may contain additives such as an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow adjuster, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, and a solvent, as necessary.
[0151] The bonding of two layers with an adhesive layer can be carried out by coating at least one of the bonding surfaces of each of the two layers with an adhesive composition, overlapping the two layers with the coating layer of the adhesive composition therebetween, pressing the layers together from above and below using a lamination roll or the like, and then drying the adhesive layer, curing it by irradiating it with active energy rays, or curing it by heating.
[0152] Before forming the coating layer of the adhesive layer, at least one of the laminating surfaces of the two layers may be subjected to an adhesion enhancing treatment such as saponification treatment, corona treatment, plasma treatment, primer treatment, anchor coating treatment, etc. Various coating methods such as a die coater, a comma coater, a gravure coater, a wire bar coater, a doctor blade coater, etc. can be used to form the coating layer of the adhesive composition.
[0153] The light irradiation intensity when irradiating with active energy rays is determined depending on the composition of the active energy ray-curable adhesive composition and is not particularly limited, but is preferably 10 mW / cm 2 More than 1,000mW / cm 2 The irradiation intensity is preferably an intensity in a wavelength region effective for activating a photocationic polymerization initiator or a photoradical polymerization initiator. Irradiation is performed once or multiple times with such a light irradiation intensity, and the integrated light amount is 10 mJ / cm or less. 2 More preferably, it is 100 mJ / cm or more. 2 More than 1,000mJ / cm 2 It is more preferable to set it as follows:
[0154] The light source used to polymerize and cure the active energy ray-curable adhesive composition is not particularly limited, but examples include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave excited mercury lamps, and metal halide lamps.
[0155] The thickness of the adhesive layer formed from the aqueous adhesive composition may be, for example, 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, and may be 0.01 μm or more, preferably 0.05 μm or more. The thickness of the adhesive layer formed from the active energy ray curable adhesive composition may be, for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, and may be 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more.
[0156] (6-2) Adhesive layer As the adhesive composition forming the adhesive layer, a conventionally known adhesive composition having excellent optical transparency can be used without any particular limitation, and for example, an adhesive composition having a base polymer such as a (meth)acrylic resin, a urethane resin, a silicone resin, or a polyvinyl ether resin can be used. In addition, it may be an active energy ray curable adhesive composition, a heat curable adhesive composition, or the like. Among these, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, removability, weather resistance, heat resistance, etc., is preferable. The adhesive composition may further contain a crosslinking agent, a silane compound, an antistatic agent, etc.
[0157] [(Meth)acrylic resin] The (meth)acrylic resin contained in the pressure-sensitive adhesive composition is preferably a polymer (hereinafter also referred to as a "(meth)acrylic acid ester polymer") having as its main component (e.g., containing 50 parts by mass or more per 100 parts by mass of the structural unit of the (meth)acrylic resin) a structural unit derived from a (meth)acrylic acid alkyl ester represented by the following formula (VIII) (hereinafter also referred to as "structural unit (VIII)"). [ka] [In formula (VIII), R 10 represents a hydrogen atom or a methyl group, R 20 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group may have any of a linear, branched, or cyclic structure, and a hydrogen atom of the alkyl group may be substituted with an alkoxy group having 1 to 10 carbon atoms.]
[0158] Examples of the (meth)acrylic acid ester represented by formula (VIII) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, i-hexyl (meth)acrylate, n-heptyl (meth)acrylate, Examples of the alkoxy group-containing alkyl acrylate include n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n- and i-nonyl (meth)acrylate, n-decyl (meth)acrylate, i-decyl (meth)acrylate, n-dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, stearyl (meth)acrylate, and t-butyl (meth)acrylate. Specific examples of the alkoxy group-containing alkyl acrylate include 2-methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and 2-methoxy-2-ethoxyethyl (meth)acrylate. In particular, the alkoxy group-containing acrylate is preferably contained in an amount of 10% by mass or more and 40% by mass or less based on the total amount of structural units constituting the (meth)acrylic resin (VIII), more preferably 15% by mass or more and 40% by mass or less, more preferably 15% by mass or more and 35% by mass or less, and particularly preferably 20% by mass or more and 35% by mass or less. If the content is less than 10% by mass, the ionic conductivity of the adhesive is low, so a large amount of antistatic agent needs to be added to ensure the desired antistatic properties, and the metal corrosion resistance is reduced, and if the content exceeds 40% by mass, the polarity of the adhesive becomes high, which increases the moisture content and affects the adhesive properties. Among them, the alkyl acrylate preferably contains n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and particularly preferably contains n-butyl (meth)acrylate. In addition, the alkoxy group-containing acrylate preferably contains 2-methoxyethyl acrylate.
[0159] The (meth)acrylic acid ester polymer may contain a structural unit derived from another monomer other than the structural unit (VIII). The structural unit derived from the other monomer may be one type or two or more types. Examples of the other monomer that the (meth)acrylic acid ester polymer may contain include a monomer having a polar functional group, a monomer having an aromatic group, and a (meth)acrylamide monomer.
[0160] The monomer having a polar functional group may be a (meth)acrylate having a polar functional group, such as a hydroxy group, a carboxy group, an amino group substituted with an alkyl group having 1 to 6 carbon atoms or an unsubstituted amino group, or a heterocyclic group such as an epoxy group.
[0161] The content of the structural units derived from monomers having a polar functional group in the (meth)acrylic acid ester polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, even more preferably 0.5 parts by mass or more and 5 parts by mass or less, and particularly preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0162] Examples of the monomer having an aromatic group include (meth)acrylic acid esters having one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) in the molecule and having a phenyl group, a phenoxyethyl group, or a benzyl group. By including these structural units, it is possible to suppress the white spot phenomenon that occurs in a polarizing plate in a high temperature and high humidity environment.
[0163] The content of the structural units derived from the monomer having an aromatic group in the (meth)acrylic acid ester polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and even more preferably 4 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0164] Examples of (meth)acrylamide monomers include N-(methoxymethyl)(meth)acrylamide, N-(ethoxymethyl)(meth)acrylamide, N-(propoxymethyl)(meth)acrylamide, N-(butoxymethyl)(meth)acrylamide, N-(2-methylpropoxymethyl)(meth)acrylamide, etc. By including these structural units, it is possible to suppress the bleeding out of additives such as antistatic agents, which will be described later.
[0165] Furthermore, as a structural unit derived from a monomer other than the structural unit (VIII), a structural unit derived from a styrene-based monomer, a structural unit derived from a vinyl-based monomer, a structural unit derived from a monomer having multiple (meth)acryloyl groups in the molecule, and the like may be included.
[0166] The weight average molecular weight (hereinafter, simply referred to as "Mw") of the (meth)acrylic resin is preferably 500,000 to 2,500,000. When the weight average molecular weight is 500,000 or more, the durability of the adhesive layer in a high temperature and high humidity environment can be improved. When the weight average molecular weight is 2,500,000 or less, the operability during application of a coating liquid containing the adhesive composition is good. In this specification, "weight average molecular weight" and "number average molecular weight" are polystyrene-equivalent values measured by gel permeation chromatography (GPC).
[0167] When the (meth)acrylic resin is dissolved in ethyl acetate to prepare a solution having a concentration of 20% by mass, the viscosity at 25° C. is preferably 20 Pa·s or less, and more preferably 0.1 to 15 Pa·s. When the viscosity of the (meth)acrylic resin at 25° C. is within the above range, the occurrence of streaks during the preparation of a pressure-sensitive adhesive layer formed from the resin can be suppressed. The viscosity can be measured by a Brookfield viscometer.
[0168] The glass transition temperature (Tg) of the (meth)acrylic resin is preferably in the range of −10 to −60° C., more preferably in the range of −20 to −50° C., and further preferably in the range of −30 to −45° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).
[0169] The (meth)acrylic resin may contain two or more kinds of (meth)acrylic acid ester polymers. Examples of such (meth)acrylic acid ester polymers include those having a weight average molecular weight smaller than that of the above-mentioned (meth)acrylic acid ester polymer having a weight average molecular weight of 500,000 to 2,500,000, and more specifically, those having a relatively low molecular weight (meth)acrylic acid ester polymer having a weight average molecular weight in the range of 50,000 to 300,000, which is mainly composed of a structural unit (VIII) derived from a (meth)acrylic acid ester.
[0170] The (meth)acrylic resin can be usually produced by a known polymerization method such as a solution polymerization method, a bulk polymerization method, a suspension polymerization method, or an emulsion polymerization method. In the production of the (meth)acrylic resin, the polymerization is usually carried out in the presence of a polymerization initiator. The amount of the polymerization initiator used is usually 0.001 to 5 parts by mass with respect to 100 parts by mass of the total of all the monomers constituting the (meth)acrylic resin. The (meth)acrylic resin can also be produced by a method of polymerization using active energy rays such as ultraviolet rays.
[0171] [Crosslinking agent] The pressure-sensitive adhesive composition preferably contains a crosslinking agent. Examples of the crosslinking agent include conventional crosslinking agents (e.g., isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.), and from the viewpoints of the pot life of the pressure-sensitive adhesive composition, crosslinking speed, and durability of the optical laminate, it is particularly preferable to use an isocyanate compound.
[0172] The isocyanate compound is a compound having at least two isocyanato groups (-NCO) in the molecule. Specific examples include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, and dimers and trimers of these isocyanate compounds are also included. Two or more types of isocyanate compounds may be combined.
[0173] The proportion of the crosslinking agent is, for example, 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and further preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0174] [Silane compounds] The pressure-sensitive adhesive composition may further contain a silane compound. Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane. The silane compound may also contain an oligomer derived from the above silane compound.
[0175] The content of the silane compound in the pressure-sensitive adhesive composition is usually 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic resin. When the content of the silane compound is 0.01 parts by mass or more, the adhesion between the pressure-sensitive adhesive layer and the adherend tends to be improved, and when the content is 10 parts by mass or less, bleeding out of the silane compound from the pressure-sensitive adhesive layer tends to be suppressed.
[0176] [Antistatic agent] The pressure-sensitive adhesive layer may contain an antistatic agent. As the antistatic agent, those shown in "(7) Pressure-sensitive adhesive layer" described later can be used.
[0177] [others] The adhesive composition may contain one or more additives such as an ultraviolet absorber, a solvent, a crosslinking catalyst, a tackifier resin, a plasticizer, etc. It is also useful to blend an ultraviolet curable compound into the adhesive composition, form an adhesive layer, and then irradiate the adhesive with ultraviolet light to cure the adhesive layer, thereby forming a harder adhesive layer.
[0178] The adhesive layer can be formed, for example, by dissolving or dispersing the adhesive composition in a solvent to prepare a solvent-containing adhesive composition, which is then applied to the surface of a substrate or a layer on which the adhesive layer is to be formed, and drying.
[0179] The thickness of the pressure-sensitive adhesive layer is usually 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm.
[0180] (7) Adhesive layer The optical laminate 1 includes a pressure-sensitive adhesive layer 5 laminated on the side of the retarder 4 opposite to the linear polarizer 2. The basic structure of the pressure-sensitive adhesive layer 5 is the same as that described above in "(6-2) Pressure-sensitive adhesive layer." Here, the antistatic agent and thickness will be described.
[0181] [Antistatic agent] The pressure-sensitive adhesive composition forming the pressure-sensitive adhesive layer 5 contains an antistatic agent, and the antistatic agent contains an ionic compound composed of an organic cation and an anion represented by the following formula (1). (C n F 2n+1 SO2)2N - …(1) (In the formula, n is an integer of 0 to 5.)
[0182] An example of the anion represented by formula (1) is the bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ] and the bis(fluorosulfonyl)imide anion [(FSO2)2N - ] anions are included.
[0183] Examples of organic cations include ammonium cations such as tributylmethylammonium cation, trioctylmethylammonium cation, trimethylpropylammonium cation, tetrabutylammonium cation, and (2-hydroxyethyl)trimethylammonium cation; phosphonium cations such as tributyldodecylphosphonium cation; pyridinium cations such as 1-hexylpyridinium cation, 1-octylpyridinium cation, 4-methyl-1-hexylpyridinium cation, 4-methyl-1-octylpyridinium cation, and 4-methyl-1-butylpyridinium cation; pyrrolidinium cations such as butylmethylpyrrolidinium cation and ethylmethylpyrrolidinium cation; imidazolium cations such as 1-ethyl-3-methylimidazolium cation and 1-butyl-3-methylimidazolium cation; pyrrolidinium cation; alkylammonium cation; sulfonium cation; etc. Among them, pyrrolidinium cation and alkylammonium cation are particularly preferred because they are difficult to move between layers of the optical laminate 1. In addition, an organic cation containing a nitrogen atom is preferable, and from the viewpoint of suppressing fluctuations in retardation characteristics when an aromatic ring-containing compound is transferred to a retarder during durability evaluation, an aliphatic cation is more preferable, and a pyrrolidinium cation or an alkylammonium cation is even more preferable.
[0184] In terms of providing excellent stability over time of the antistatic performance of the pressure-sensitive adhesive composition, an ionic compound that is solid at room temperature (having a melting point of 23° C. or higher) is preferred. The molecular weight of the ionic compound is not particularly limited, but is preferably, for example, 700 or less, more preferably 500 or less.
[0185] The content of the antistatic agent is, for example, 0.01 to 20 parts by mass, preferably 0.1 to 10 parts by mass, more preferably 0.1 to 2.5 parts by mass, and even more preferably 0.1 to 1.5 parts by mass, relative to 100 parts by mass of the non-volatile content of the resin constituting the pressure-sensitive adhesive layer. When the antistatic agent is contained in an amount of 0.1 part by mass or more, the antistatic performance is improved, and when the amount is 10 parts by mass or less, bleeding out of the ionic compound from the pressure-sensitive adhesive layer during a durability test can be suppressed, and durability can be easily maintained, which is preferable.
[0186] The thickness T3 of the pressure-sensitive adhesive layer 5 is usually 5 μm or more, and preferably 10 μm or more. The thickness T3 of the pressure-sensitive adhesive layer 5 is usually 35 μm or less, and preferably 30 μm or less.
[0187] <Image display device> The image display device includes the optical laminate according to the present invention and an image display element (such as an organic EL display element). The optical laminate is disposed on the viewing side of the image display element. The optical laminate can be attached to the image display element using the pressure-sensitive adhesive layer 5.
[0188] The image display device is not particularly limited, and examples thereof include image display devices such as organic electroluminescence (organic EL) display devices, inorganic electroluminescence (inorganic EL) display devices, liquid crystal display devices, and electroluminescence display devices.
[0189] The image display device can be used as mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signs, measuring instruments or gauges, office equipment, medical equipment, computing equipment, and the like.
[0190] Although the preferred embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. In the optical laminate 1 of the above embodiment, the outermost layers are the first protective film 21 and the adhesive layer 5, but if necessary, the first protective film 21 may be provided with a surface protective film for protecting its surface, and the adhesive layer 5 may be provided with a separator. EXAMPLES
[0191] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the following examples. In the following description, parts and percentages representing the amount used and the content are based on mass unless otherwise specified. In addition, in the following description, the numbers in "second protective film 3", "adhesive layer 1", etc. represent the types of the multiple types of second protective films, adhesive layers, etc. used, and are unrelated to the symbols in the drawings.
[0192] <Measurement and Evaluation> (1) Thickness of layer or film Unless otherwise specified, the thickness of a layer or film was measured using a laser microscope ("LEXT" manufactured by Olympus Corporation) or a digital micrometer ("MH-15M" manufactured by Nikon Corporation).
[0193] (2) In-plane retardation value of layer or film The in-plane retardation values [nm] of the layer or film at wavelengths of 550 nm and 450 nm were measured using a retardation measuring device (KOBRA-WPR, manufactured by Oji Scientific Instruments Co., Ltd.).
[0194] (3) Moisture permeability of protective film The moisture permeability of the second protective film was measured under the following measurement conditions. Test item: Water vapor permeability Test method: Moisture sensor method Measurement equipment: Lyssy L80 series water vapor transmission meter Sample preparation method: After attaching an aluminum mask to the second protective film surface of a laminate including a supporting substrate and a second protective film, which will be described later, the supporting substrate was peeled off, and an aluminum mask was attached to the peeled off surface to prepare a measurement sample. The second protective film 8 (a triacetyl cellulose film having a thickness of 20 μm) used in Comparative Example 1 does not have a supporting substrate, so the supporting substrate was not peeled off. Measurement conditions Measurement temperature: 40℃ Relative humidity: 90%RH Measurement area: Second protective film 1-4: 7.1 x 10 -4 m 2 (Transmission area when wearing a mask) Second protective film 5: 7.9 x 10 -5 m 2 (Transmission area when wearing a mask) Measurement sample installation direction: Any
[0195] (4) Water vapor permeability coefficient of retarder The water vapor permeability coefficient of the phase shifter was measured in the same manner as in (3) above, except that the measurement temperature was 65°C. 2 This was calculated by multiplying the heat capacity (unit: mm) by the thickness.
[0196] (5) Evaluation of phase difference change The change in the in-plane retardation value when the optical laminate was placed in a high-temperature, humid, and hot environment was measured and evaluated according to the following procedure. A 30 mm x 30 mm sample with the retarder's slow axis in the long side direction was cut out from the optical laminate. The sample was attached to alkali-free glass (manufactured by Corning, product number: EAGLE XG (registered trademark)) via the antistatic adhesive layer of the sample to prepare an evaluation sample. The in-plane retardation values at wavelengths of 550 nm and 450 nm were measured for the evaluation sample using a retardation measuring device (manufactured by Oji Scientific Instruments, KOBRA-WPR). The obtained values were used to calculate the change in the in-plane retardation value ΔRe (550) and the wavelength dispersion α (in-plane retardation value Re (450) / in-plane retardation value Re (550)). Five evaluation samples were measured, and the average value was calculated.
[0197] The evaluation sample was placed in an oven and subjected to a 336-hour moist heat durability test at a temperature of 60° C. and a relative humidity of 90% RH. The evaluation sample was removed from the oven, and 3 hours later, the in-plane retardation values at wavelengths of 550 nm and 450 nm were measured using the retardation measurement device described above, and the change in the in-plane retardation value ΔRe(550) before and after the heat resistance test was calculated. A: ΔRe(550) is less than 0.5 B: ΔRe(550) is 0.5 or more and less than 0.7 C: ΔRe(550) is 0.7 or more
[0198] The evaluation sample was placed in an oven and subjected to a 504-hour moist heat durability test at a temperature of 60°C and a relative humidity of 90%RH. The evaluation sample was removed from the oven, and 3 hours later, the in-plane retardation values at wavelengths of 550 nm and 450 nm were measured using the retardation measurement device described above. The amount of change was calculated from the chromatic dispersion α (0 hours) before the heat resistance test and the chromatic dispersion α (504 hours) after the heat resistance test, and Δα, the rate of change in α, was calculated according to the following formula. Of the following criteria, A indicates the smaller change in chromatic dispersion α. Δα(%)=(α(504 hours)-α(0 hours)) / α(0 hours)×100 A: |Δα| is less than 0.2 B: |Δα| is 0.2 or more
[0199] (6) Evaluation of metal corrosion using optical laminates A metal-layered glass substrate was prepared by laminating a metal aluminum layer and a metal titanium layer in this order on the surface of an alkali-free glass substrate by sputtering. Next, the optical laminate obtained in the examples and comparative examples was cut into a size of 50 mm x 50 mm, and the metal titanium layer side of the metal-layered glass substrate was attached to the adhesive layer of the optical laminate to prepare an evaluation sample. The evaluation sample was stored in an oven at a temperature of 85°C and a relative humidity of 85%RH for 350 hours, and then the evaluation sample was removed from the oven. The evaluation sample was placed on a backlight with the glass substrate facing down, and the number and size of bright spots due to light leakage were observed, and metal corrosion was evaluated according to the following criteria. A+: No bright spots A: 1 to 5 bright spots of 0.1 to 0.5 mm B+: 6 to 15 bright spots of 0.1 to 0.5 mm or less, or 5 bright spots of 0.5 to 1.0 mm or less B: 6 to 15 bright spots of 0.5 to 1.0 mm C: More than 15 bright spots are observed over the entire surface, but there are some areas where there are no bright spots.
[0200] [Preparation of polarizer] (1) Preparation of polarizer 1 A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99.9% or more was uniaxially stretched to a stretching ratio of 4.5 times in a dry state, and while maintaining a tension state, it was immersed for 60 seconds in a dye bath at 28°C containing 0.05 parts of iodine and 5 parts of potassium iodide per 100 parts of water.
[0201] Next, the film was immersed for 110 seconds in a boric acid aqueous solution 1 at 64° C. containing 5.5 parts of boric acid and 15 parts of potassium iodide per 100 parts of water. Next, the film was immersed for 30 seconds in a boric acid aqueous solution 2 at 67° C. containing 5.5 parts of boric acid and 15 parts of potassium iodide per 100 parts of water. Thereafter, the film was washed with pure water at 3° C. and dried to obtain a polarizer 1. The boron content of the polarizer 1 measured by the above method was 4.1% by mass. The thickness of the polarizer was 8 μm.
[0202] (2) Preparation of polarizer 2 A 30 μm thick polyvinyl alcohol resin film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched vertically by about 5 times by dry stretching, and then, while maintaining the tension, was immersed in pure water at a temperature of 60° C. for 1 minute, and then, was immersed in an aqueous solution at a temperature of 28° C. in which the mass ratio of iodine / potassium iodide / water was 0.05 / 5 / 100 for 60 seconds. Then, it was immersed in an aqueous solution at a temperature of 72° C. in which the mass ratio of potassium iodide / boric acid / water was 8.5 / 8.5 / 100 for 300 seconds. It was then washed with pure water at a temperature of 26° C. for 20 seconds, and then, was dried at a temperature of 65° C. to obtain a linear polarizer having a thickness of 12 μm in which iodine was adsorbed and aligned on the polyvinyl alcohol resin film.
[0203] [Protective film production and preparation] (1) Preparation of First Protective Film 1 As the first protective film 1, a triacetyl cellulose (TAC) film (KC2UATAC manufactured by Konica Minolta, Inc., thickness T1: 25 μm) having a 7 μm-thick hard coat layer (thickness T1: 32 μm) formed on one side thereof was prepared.
[0204] (2) Preparation of second protective film 1 A polyethylene terephthalate film (PET film) having a thickness of 38 μm ("TN100" manufactured by Toyobo Co., Ltd., having a release layer containing a non-silicone release agent) was prepared as a supporting substrate. The following components were mixed to prepare a composition containing a thermoplastic resin. Cyclic polyolefin resin (ZEON Corporation's "ZEONOR ZF14"): 10 parts Cyclohexane: 90 parts
[0205] A composition containing the above thermoplastic resin was applied onto the release layer of the supporting substrate using a die by a backcoat method, and the applied layer was dried under conditions of 40°C for 1 minute, 70°C for 1 minute, and 120°C for 2 minutes to produce a laminate having a cyclic polyolefin resin layer with a thickness T2 of 2 μm as the second protective film 1. The moisture permeability of the second protective film 1 was 63 g / m 2 / 24hr.
[0206] (3) Preparation of second protective film 2 A laminate having a cyclic polyolefin resin layer with a thickness T2 of 3 μm was prepared as the second protective film 2 in the same manner as the preparation of the second protective film 1, except that the amount of the composition containing a thermoplastic resin applied onto the release layer of the support substrate was changed. The moisture permeability of the second protective film 2 was 37 g / m 2 / 24hr.
[0207] (4) Preparation of second protective film 3 A laminate having a cyclic polyolefin resin layer with a thickness T2 of 4 μm was produced as the second protective film 3 in the same manner as the production of the second protective film 1, except that the amount of the composition containing a thermoplastic resin applied onto the release layer of the support substrate was changed. The moisture permeability of the second protective film 3 was 19 g / m 2 / 24hr.
[0208] (5) Preparation of second protective film 4 A cyclic polyolefin resin film having a thickness T2 of 13 μm was prepared as the second protective film 4. The moisture permeability of the second protective film 4 was 4.8 g / m 2 / 24hr.
[0209] (6) Preparation of second protective film 5 A triacetyl cellulose film having a thickness of 25 μm was prepared as the second protective film 5. The moisture permeability of the second protective film 5 was 1280 g / m2 / 24 hr.
[0210] [Preparation of active energy ray curable adhesive] (1) Preparation of active energy ray curable adhesive 1 The components below were blended and mixed, and then degassed to prepare an active energy ray-curable adhesive 1 (hereinafter simply referred to as "adhesive 1"). (cationically polymerizable compound) 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts (Photocationic polymerization initiator) Product name: CPI-100 (San-Apro Co., Ltd., 50% propylene carbonate solution): 4.5 parts (actual solid content 2.25 parts) (Photosensitizer assistant) 1,4-diethoxynaphthalene: 2 parts
[0211] [Preparation of adhesive layer] The following adhesive layer 1 and adhesive layer 2 were prepared, both of which had release films attached to them. (1) Preparation of adhesive layer 1 The pressure-sensitive adhesive layer 1 was prepared by the following procedure. In the examples described later, the pressure-sensitive adhesive layer 1 is mainly used as an adhesive layer between a linear polarizer and a phase shifter, and in some examples, it is used as an adhesive layer within the phase shifter.
[0212] (1-1) Preparation of acrylic resin solution 1 A mixed solution of 100 parts of ethyl acetate, 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, and 0.5 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while raising the internal temperature to 55°C. Then, a solution of 0.12 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56°C, and the addition of ethyl acetate was stopped when the concentration of the acrylic resin reached 35% by mass, and the temperature was kept at this temperature until 6 hours had passed since the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20% by mass, and acrylic resin solution 1 was prepared. The weight average molecular weight Mw of the obtained acrylic resin was 1.7 million. The Mw was measured in terms of standard polystyrene using two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns in the GPC apparatus, tetrahydrofuran as the eluent, a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40° C., and a flow rate of 1 mL / min.
[0213] (1-2) Preparation of Pressure Sensitive Adhesive Composition 1 To 80 parts of the solid content of the acrylic resin solution 1 obtained in (1-1) above, 20 parts (solid content) of a bifunctional acrylate (obtained from Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts of a crosslinking agent (manufactured by Mitsui Chemicals: product name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75 mass%)) based on active ingredients, 1.5 parts of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: product name "Irgacure 500"), and 0.3 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.: product name "KBM-403") were added, and ethyl acetate was further added so that the solid content concentration became 13%, thereby obtaining a pressure-sensitive adhesive composition 1.
[0214] A-DOG is a diacrylate of an acetal compound of hydroxypivalaldehyde and trimethylolpropane and has the structure of the following formula. [Chemical formula]
[0215] (1-3) Preparation of the adhesive layer 1 The adhesive composition 1 prepared in the above (1-2) was applied to the release-treated surface of a release film made of a polyethylene terephthalate film [manufactured by Mitsubishi Chemical Corporation: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness T3 after drying was 5 μm, and dried at 100 °C for 1 minute to prepare an adhesive layer (adhesive sheet). Next, the surface of the obtained adhesive layer on the side opposite to the release film side was bonded to the release-treated surface of a release film made of a polyethylene terephthalate film [manufactured by Mitsubishi Chemical Corporation: MRF (thickness: 38 μm)]. Subsequently, ultraviolet rays were irradiated under the following conditions to prepare the adhesive layer 1. The storage elastic modulus G' of the adhesive layer 1 at a temperature of 85 °C was 0.125 MPa. [UV irradiation conditions] ·Using a Fusion UV lamp system (manufactured by Fusion UV Systems) H bulb ·Integrated light amount of UV wavelength region UVA 250 mJ / cm 2 (Measured value by UV Power PuckII manufactured by FusionUV)
[0216] (2) Preparation of the adhesive layer 2 The acrylic adhesive layer 2 was prepared by the following procedure. The adhesive layer 2 contains an antistatic agent and is used as an adhesive layer to be bonded to the side opposite to the linear polarizer side of the phase element in the examples described later.
[0217] (2-1) Preparation of the acrylic resin solution 2 A monomer mixture prepared by diluting 42.5 parts by mass of n-butyl acrylate, 5 parts by mass of 2-ethylhexyl acrylate, 20 parts by mass of methyl acrylate, 30 parts by mass of 2-methoxyethyl acrylate, 1.0 part by mass of 2-hydroxyethyl acrylate, and 1.5 parts by mass of acrylic acid with ethyl acetate was charged into a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer, and the air in the vessel was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 55° C. Then, a solution of azobisisobutyronitrile dissolved in ethyl acetate as a polymerization initiator was added so that the amount of azobisisobutyronitrile was 0.3 parts by mass per 100 parts by mass of the total amount of monomers. After the addition of the polymerization initiator, the temperature was kept at 55°C for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54-56°C. When the concentration of the acrylic resin reached 35%, the addition of ethyl acetate was stopped, and the temperature was kept at 55°C for 12 hours from the start of the addition of ethyl acetate. After that, ethyl acetate was added to adjust the concentration of the acrylic resin to 20%, and acrylic resin solution 2 was prepared. The weight average molecular weight Mw of the obtained acrylic resin was 1.58 million.
[0218] (2-2) Preparation of Pressure Sensitive Adhesive Composition 2 Adhesive composition 2-1 To 100 parts by mass of the solid content of the acrylic resin solution 2 obtained above, 0.5 parts by mass of a crosslinking agent (trade name "D-103" manufactured by Mitsui Chemicals, Inc.) (a solution of an ethyl acetate adduct of tolylene diisocyanate (solid content concentration 75% by mass) based on the active ingredient, 0.5 parts by mass of a silane compound (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) (3-glycidoxypropyltrimethoxysilane) based on the active ingredient, and 0.54 parts by mass of an ionic compound (tributylmethylammonium bis(trifluoromethanesulfonyl)imide) based on the active ingredient were added, and ethyl acetate was further added so that the solid content concentration became 14%, to obtain a pressure-sensitive adhesive composition 2-1 for producing a pressure-sensitive adhesive layer "AS-PSA1" described later. Adhesive composition 2-2 Pressure-sensitive adhesive composition 2-2 for producing the pressure-sensitive adhesive layer "AS-PSA2" described below was obtained in the same manner as in the preparation of "(AS-PSA1)" above, except that the ionic compound was changed to butylmethylpyrrolidinium bis(trifluoromethanesulfonyl)imide (0.47 parts by mass based on the active ingredient). Adhesive composition 2-3 Pressure-sensitive adhesive composition 2-3 for producing the pressure-sensitive adhesive layer "AS-PSA3" described later was obtained in the same manner as in the preparation of "(AS-PSA1)" above, except that the ionic compound was changed to 4-methyl-1-octylpyridinium bis(trifluoromethanesulfonyl)imide in an amount of 0.51 parts by mass based on the active ingredient. Adhesive composition 2-4 Pressure-sensitive adhesive composition 2-4 for producing the pressure-sensitive adhesive layer "AS-PSA4" described later was obtained in the same manner as in the preparation of "(AS-PSA1)" above, except that the ionic compound was changed to 4-methyl-1-octylpyridinium hexafluorophosphate in an amount of 0.41 parts by mass based on the active ingredient.
[0219] (2-3) Preparation of adhesive layers AS-PSA1, AS-PSA2, AS-PSA3, and AS-PSA4 The adhesive composition 2-1 obtained above was applied to the release-treated surface of a release film (1) (manufactured by Mitsubishi Chemical Corporation, product name "MRV38 (V04)", thickness: 38 μm) using an applicator so that the thickness after drying would be 15 μm, and then dried at a temperature of 100 ° C. for 1 minute to obtain an adhesive layer (1) having a thickness of 15 μm. A release film (2) (manufactured by Mitsubishi Chemical Corporation, product name "MRF38", thickness: 38 μm) was laminated on the opposite side of the obtained adhesive layer (1) from the release film (1) so that the release-treated surface was on the adhesive layer (1) side. The obtained laminate was left to stand for 7 days or more under an environment of a temperature of 23 ° C. and a relative humidity of 60%, to obtain an adhesive layer AS-PSA1. In addition, adhesive layers AS-PSA2, AS-PSA3, and AS-PSA4 were obtained in the same manner as above, except that adhesive compositions 2-2, 2-3, and 2-4 were used as the adhesive compositions, respectively. These pressure-sensitive adhesive layers AS-PSA1, AS-PSA2, AS-PSA3, and AS-PSA4 are collectively referred to as "pressure-sensitive adhesive layer 2."
[0220] [Preparation of phase shifter] (1) Preparation of retardation film A (1-1) Preparation of composition A for forming photoalignment film The photo-alignment material (weight average molecular weight: 50,000, m:n = 50:50) having the following structure was produced according to the method described in JP 2021-196514 A. Two parts of the photo-alignment material and 98 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80 ° C. for 1 hour to prepare a composition A for forming a photo-alignment film. Photoalignable materials: [ka]
[0221] (1-2) Preparation of polymerizable liquid crystal compound The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) having the structures shown below were prepared. The polymerizable liquid crystal compound (A1) was prepared in the same manner as described in JP-A-2019-003177. The polymerizable liquid crystal compound (A2) was prepared in the same manner as described in JP-A-2009-173893. Polymerizable liquid crystal compound (A1): [ka] Polymerizable liquid crystal compound (A2): [ka]
[0222] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (A1) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.
[0223] (1-3) Preparation of Retardation Film-Forming Composition A The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of a photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) were added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13%. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film-forming composition A.
[0224] (1-4) Preparation of Retardation Film A The photo-alignment film-forming composition A was applied to a biaxially oriented polyethylene terephthalate (PET) film (Diafoil; manufactured by Mitsubishi Plastics, Inc.) as the substrate A using a bar coater. The resulting coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to form a dry film. Thereafter, the film was irradiated with 100 mJ of polarized ultraviolet light (based on 313 nm) using a UV irradiation device (SPOT CURE SP-9; manufactured by Ushio Inc.) to obtain a photo-alignment film A. The thickness of the photo-alignment film A measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100 nm.
[0225] The above-mentioned retardation film-forming composition A was applied onto the obtained photo-alignment film A using a bar coater to form a coating film. This coating film was dried by heating at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.), the exposure amount was 500 mJ / cm2 in a nitrogen atmosphere. 2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film A in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, thereby obtaining a laminate A consisting of substrate A / photo-alignment film A / retardation film A. The thickness of retardation film A was 2.0 μm as measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation.
[0226] The surface of the retardation film A of the laminate A was subjected to a corona treatment, and the laminate was attached to glass via a 25 μm-thick adhesive layer (manufactured by Lintec Corporation), and the substrate A was peeled off and removed. The in-plane retardation values for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from Cauchy's dispersion formula obtained from the measurement results of the in-plane retardation values for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. As a result, the in-plane retardation values were Re(450)=122 nm, Re(550)=140 nm, and Re(650)=144 nm, and the relationship between the in-plane retardation values at each wavelength was as follows: Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.)
[0227] (2) Preparation of retardation film B (2-1) Preparation of composition B for forming alignment layer A composition B for forming an alignment film was obtained by adding 2-butoxyethanol to a commercially available alignment polymer, Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), so that the solid content was 1%.
[0228] (2-2) Preparation of Retardation Film-Forming Composition B 100 parts of polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan Co., Ltd.), 0.1 parts of leveling agent "BYK-361N" (manufactured by BYK-Chemie Co., Ltd.), and 2.5 parts of photopolymerization initiator "Omnirad907" (manufactured by IGM Resin BV Co., Ltd.) were mixed. Furthermore, 400 parts of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the resulting mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film forming composition B. Polymerizable liquid crystal compound LC242: [ka]
[0229] Fabrication of (2-3) retardation film B As the substrate B, a cyclic olefin resin (COP) film (ZF14, manufactured by Nippon Zeon Co., Ltd.) was used. Corona treatment was performed on one side thereof using a corona treatment apparatus (AGF-B10; manufactured by Kasuga Electric Co., Ltd.). The composition B for forming an alignment film was applied to the surface using a bar coater and dried at 90°C for 1 minute. When the film thickness of the obtained alignment film B was measured with a laser microscope, it was 30 nm.
[0230] The composition B for forming a retardation film was applied onto the obtained alignment film B using a bar coater and dried at 90°C for 1 minute to obtain a dried film. Using a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by Ushio Inc.), ultraviolet light with an exposure amount of 1000 mJ / cm 2 (standard at 365 nm) was irradiated onto the dried film to form a retardation film B, and a laminate B composed of substrate B / alignment film B / retardation film B was obtained. The film thickness of the retardation film B measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation was 450 nm.
[0231] When the retardation value was measured, Re(550) = 1 nm and Rth(550) = -75 nm. The laminate B had optical properties represented by nx ≒ ny < nz. Since the retardation value of COP at a wavelength of 550 nm is approximately 0, it does not affect the said optical properties.
[0232] Fabrication of (3) phase element 1 The retardation film A of the laminate A and the retardation film B of the laminate B were each subjected to a corona treatment. An adhesive was applied to the corona-treated surface of either the retardation film A or the retardation film B, and the laminate A and the laminate B were bonded together. The adhesive 1 described above was used as the adhesive. The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was carried out once using the corona treatment device described above under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The adhesive 1 was cured by irradiating ultraviolet rays from the laminate A side, forming an adhesive layer 1 having a thickness of 1.5 μm. The ultraviolet rays were UVA with a wavelength of 320 nm to 390 nm at 420 mJ / cm. 2 By the above, a retarder 1 with a substrate, which is composed of substrate A / photo-alignment film A / retardation film A / adhesive layer 1 / retardation film B / alignment film B / substrate B, was produced.
[0233] (4) Fabrication of phase shifter 2 Retarder 2 was produced in the same manner as retarder 1, except that in the production of retarder 1, laminate A and laminate B were bonded together using pressure-sensitive adhesive layer 1 instead of adhesive 1 to produce a retarder. In this manner, retarder 2 with a substrate, consisting of substrate A / photo-alignment film A / retardation film A / pressure-sensitive adhesive layer 1 / retardation film B / alignment film B / substrate B, was produced.
[0234] <Examples 1 to 12, Comparative Example 1> The first protective film 1 prepared above, a polarizer selected from the polarizers 1 and 2, a protective film selected from the second protective films 1 to 5, and a retarder selected from the retarders 1 and 2 were bonded together. Next, a pressure-sensitive adhesive layer was laminated on the surface of the retarder opposite to the second protective film side to obtain optical laminates of Examples 1 to 12 and Comparative Example 1. Specifically, the process is as follows.
[0235] The surfaces of the first protective film and the second protective film (when a laminate having a second protective film was used, the surface of the second protective film of the laminate) were each subjected to a corona treatment. A water-based adhesive was applied to one side of the polarizer, and the first protective film was attached to it. A water-based adhesive was applied to the other side of the polarizer, and the second protective film (or a laminate having a second protective film) was attached to it. Then, the polarizing plate was obtained by drying. The water-based adhesive was obtained by dissolving 3 parts of carboxyl group-modified polyvinyl alcohol (trade name "KL-318" obtained from Kuraray Co., Ltd.) in 100 parts of water, and adding 1.5 parts of a polyamide epoxy-based additive, which is a water-soluble epoxy resin (trade name "Sumirez Resin 650 (30)" manufactured by Taoka Chemical Co., Ltd., an aqueous solution with a solid content concentration of 30%). As a result, a laminate X (linear polarizing plate) consisting of a first protective film / adhesive layer / polarizer / adhesive layer / second protective film was obtained. Here, when a laminate having a second protective film is used, the laminate X has a structure of first protective film / adhesive layer / polarizer / adhesive layer / second protective film / supporting substrate.
[0236] Next, the surface of the second protective film of the laminate X (when the laminate X has a supporting substrate, the surface from which the supporting substrate is peeled off) and the surface exposed by peeling off the substrate A of the retarder were each subjected to a corona treatment. The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was performed once using the corona treatment device under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface of the laminate X and the corona-treated surface of the retarder were bonded together via the pressure-sensitive adhesive layer 1. Thereafter, the substrate B of the retarder was peeled off and removed to obtain a laminate Y including the first protective film / adhesive layer / polarizer / adhesive layer / second protective film / adhesive layer 1 / photo-alignment film A / retardation film A / adhesive layer inside the retarder / retardation film B / alignment film B in this order. Finally, the pressure-sensitive adhesive layer 2 was laminated on the surface of the laminate Y on the retardation film B side to obtain an optical laminate. The obtained optical laminate was evaluated using a retardation measuring device (KOBRA-WPR, manufactured by Oji Scientific Instruments), and the in-plane retardation value and wavelength dispersion of the retarder were Re(550)=140 nm and α=0.87, respectively.
[0237] The following table shows the types of the first protective film, polarizer, second protective film, retarder, and pressure-sensitive adhesive layer (the pressure-sensitive adhesive layer laminated on the surface of the retarder opposite to the second protective film) used in Examples 1 to 12 and Comparative Example 1. The following table also shows the results of evaluation of the amount of change in retardation and metal corrosion performed on each optical laminate.
[0238] [Table 1]
[0239] [Table 2]
[0240] From the results shown in Tables 1 and 2, it was found that when the moisture permeability of the second protective film is low and the adhesive layer contains a predetermined antistatic material, the change in the retardation characteristics and metal corrosion are sufficiently suppressed (comparison between Examples 1 to 12 and Comparative Example 1). In addition, it was found that when the adhesive layer 1 was used as the adhesive layer in the retarder, the degree of suppression of metal corrosion was slightly weakened (Examples 7, 10, and 12). It was also found that when the thickness of the second protective film was increased, the degree of suppression of metal corrosion was slightly weakened (Examples 9 to 12). It was also found that when the thickness of the second protective film was too thin, the degree of suppression of metal corrosion was slightly weakened (Examples 2 and 5). [Industrial Applicability]
[0241] The present invention can be used as a circular polarizing plate. [Explanation of symbols]
[0242] 1...optical laminate, 2...linear polarizing plate, 3...adhesive layer between linear polarizing plate and retarder, 4...retarder, 5...adhesive layer, 21...first protective film, 22...polarizer, 23...second protective film, 41...first retardation layer, 42...adhesive layer in retarder, 43...second retardation layer.
Claims
1. An optical laminate including a first protective film, a polarizer, a second protective film, a retarder, and a pressure-sensitive adhesive layer in this order, The moisture permeability of the second protective film is 1200 g / (m 2 ・day) or less, The pressure-sensitive adhesive layer contains an antistatic agent, The antistatic agent comprises an ionic compound having an organic cation and an anion represented by the following formula (1): (C n F 2n+1 SO 2 ) 2 N - …(1) (In the formula, n is an integer from 0 to 5.)
2. The optical laminate according to claim 1 , wherein the water vapor permeability coefficient of the retarder is 100 or less.
3. The optical laminate according to claim 1 , wherein the retarder comprises a first retardation layer, a pressure-sensitive adhesive layer, and a second retardation layer, and has a function as a λ / 4 plate over the entire visible light range.
4. The optical laminate according to claim 3 , wherein the adhesive layer is made of an active energy ray-curable adhesive.
5. The optical laminate according to claim 1 , wherein the second protective film is made of a cyclic polyolefin resin.
6. The optical laminate according to claim 1, wherein the second protective film has a thickness of 1 to 10 μm.
7. The moisture permeability of the first protective film is 100 g / (m 2 2. The optical laminate according to claim 1, wherein the optical performance is at least 100%.
8. The optical laminate according to claim 1 , wherein the ionic compound comprises an organic cation containing a nitrogen atom.
9. The optical laminate according to any one of claims 1 to 8, and an image display panel to which the optical laminate is attached.
Citation Information
Patent Citations
Polymerizable liquid crystal composition, optical anisotropic layer, retardation film, polarizing plate, laminate, liquid crystal display device and organic electroluminescence device
JP2020084070A
Polarizing plate with retardation layer and adhesive layers, and organic electroluminescence display device using the same
JP2021063972A
Polarizing plate with retardation layer and organic electroluminescence display device using the same
JP2021063975A
Circularly polarizing plate and image display device using the same
JP2022134862A
Polarizing film with added adhesive layer, polarizing film with added adhesive layer for in-cell liquid crystal panel, in-cell liquid crystal panel, and liquid crystal display device
WO2018181416A1
